Antimicrobial efficacy, mode of action and in vivo use of hypochlorous acid (HOCl) for prevention or therapeutic support of infections - Boecker, Dirk; Zhang, Zhentian; Breves, Roland; Herth, Felix; Kramer, Axel; Bulitta, Clemens (German Medical Science GMS Publishing House, 2023)
The objective is to provide a comprehensive overview of the rapidly developing field of the current state of research on use of hypochlorous acid (HOCl) to aid infection prevention and control, including naso-pharyngeal, alveolar, topical, and systemic HOCl applications. Also, examples are provided of dedicated applications in COVID-19. A brief background of HOCl's biological and chemical specifics and its physiological role in the innate immune system is provided to understand the effect of applications in the context of the body's own physiological defense mechanisms.